2022
DOI: 10.3390/molecules27061992
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Determination of Tenofovir in Pharmaceutical Formulations and Patients Urine—Comparative Electroanalytical Studies Using Different Sensing Methods

Abstract: This paper discusses the electrochemical behavior of antiviral drug Tenofovir (TFV) and its possible applicability towards electroanalytical determination with diverse detection strategies using square-wave voltammetry. Namely, oxidation processes were investigated using glassy carbon electrode with graphene oxide surface modification (GO/GCE), while the reduction processes, related to the studied analyte, were analyzed at a renewable silver amalgam electrode (Hg(Ag)FE). Scanning electron microscopy imaging co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Combined with the conclusion obtained from the pH, it can be seen that the electrochemical oxidation of TDF on the electrode is a two-electron and two-proton transfer process. According to the existing reports on the oxidation mechanism of TFV (of which TDF is a precursor) [ 65 , 66 ], it can be speculated that the oxidation mechanism of TDF on ZrO 2 -CS-MWCNTs/GCE is as shown in Figure S4 .…”
Section: Resultsmentioning
confidence: 99%
“…Combined with the conclusion obtained from the pH, it can be seen that the electrochemical oxidation of TDF on the electrode is a two-electron and two-proton transfer process. According to the existing reports on the oxidation mechanism of TFV (of which TDF is a precursor) [ 65 , 66 ], it can be speculated that the oxidation mechanism of TDF on ZrO 2 -CS-MWCNTs/GCE is as shown in Figure S4 .…”
Section: Resultsmentioning
confidence: 99%
“…This approach offers a considerable advantage over conventional methods such as LC-MS/MS, which involve complex instrumentation and sample preparation (Lin et al, 2023). Other methods of detection of aqueous TFV include squarewave voltammetry where Festinger and coworkers reported limits of detection as low as 1.35 × 10 −7 M (39 ng/mL) and 4.86 × 10 −8 M (14 ng/ mL) (Festinger et al, 2022). Chiral separation phase (CSP) LCMS of enantiomeric mixtures of a prodrug form of tenofovir, tenofovir disoproxil fumarate (TDF), reported limits of detection of 1.5 ng/ mL and 1.2 ng/mL for the R-and S-TDF enantiomers, respectively (Lin et al, 2023).…”
Section: ρ αEmentioning
confidence: 99%
“…23 Nanomaterial based modications are gaining popularity due to their unique characteristics such as fast electron transfer, nanosize, stability, energy efficiency, and catalytic performance. 24 Some studies have explored the electrochemical detection of TFV drugs using nanomaterials: Xiao et al reported ZrO 2 -CS-MWCNTs/GCE, 2 Mehmandoust et al reported MIP-PT@g-C 3 N 4 /F-MWCNT, 9 Alake et al developed an electrode with NiS@PAA-MWCNT, 13 Zeng et al used La 2 O 3 -ZrO 2 -MWCNTs/ GCE, 11 Festinger et al proposed GO/GCE and Hg(Ag)FE, 25 and Ozcelikay et al utilized benzalkonium chloride/AgNPs. 26 It is imperative to conduct a thorough assessment in order to obtain accurate and timely detection of the TFV drug with a costeffective and feasible implementation.…”
Section: Introductionmentioning
confidence: 99%